A Vision for Change: Speeches and Writings of AD Patel, 1929-1969 - V. Lal, Brij (ANU Press, 2011)
"This collection of the writings and speeches of one of Fiji's greatest statesmen, the late Mr AD Patel, points to a different future which, if allowed to come to fruition, would have spared Fiji the fate it later encountered in its postcolonial journey. As a leader, Mr Patel was unmatchable in intellect and oratorical brilliance, glimpses of which we see in this volume. Dr Lal deserves to be congratulated for his patience and perseverance in completing this project. This book will find an honoured place among others on Fiji's complex and contested modern history."